Dissecting the biophysical mechanisms of oleate hydratase association with membranes - William A. Lathram; Robert J. Neff; Ashley N. Zalla; James D. Brien; Vivekanandan Subramanian; Christopher D. Radka (Frontiers in Molecular Biosciences)
This study investigates the dynamics of oleate hydratase (OhyA), a bacterial flavoenzyme from Staphylococcus aureus, and its interactions with lipid membranes, focusing on the factors influencing membrane binding and oligomerization. OhyA catalyzes the hydration of unsaturated fatty acids, playing a key role in bacterial pathogenesis by neutralizing host antimicrobial fatty acids. OhyA binds the membrane bilayer to access membrane-embedded substrates for catalysis, and structural studies have revealed that OhyA forms oligomers on membrane surfaces, stabilized by both protein-protein and protein-lipid interactions. Using fluorescence correlation spectroscopy (FCS), we examined the effects of membrane curvature and lipid availability on OhyA binding to phosphatidylglycerol unilamellar vesicles. Our results reveal that OhyA preferentially binds to vesicles with moderate curvature, while the presence of substrate fatty acids slightly enhanced the overall interaction despite reducing the binding affinity by 3- to 4-fold. Complementary phosphorus-31 (31P) NMR spectroscopy further demonstrated two distinct binding modes: a fast-exchange interaction at lower protein concentrations and a longer lasting interaction at higher protein concentrations, likely reflecting cooperative oligomerization. These findings highlight the reversible, non-stoichiometric nature of OhyA•membrane interactions, with dynamic binding behaviors influenced by protein concentration and lipid environment. This research provides new insights into the dynamic behavior of OhyA on bacterial membranes, highlighting that initial interactions are driven by lipid-mediated protein binding, while sustained interactions are primarily governed by the protein:lipid molar ratio rather than the formation of new, specific lipid-protein interactions. These findings advance our understanding of the biophysical principles underlying OhyA’s role in bacterial membrane function and virulence.